South Africa, Lesotho & Swaziland - Bainbridge, James; Carillet, Jean-Bernard; Corne, Lucy; Murphy, Alan; Phillips, Matt; Richmond, Simon (Footscray, Victoria, Australia Lonely Planet Publications Pty Limited, 2015)
The only guide to include coverage of Lesotho and Swaziland. South Africa is a growth tourist destination. Includes detailed full-colour maps.
Previously entered under title: South Africa, Lesotho & Swaziland : a Lonely Planet travel survival kit.
R-5785 arbitrarily numbered.
At head of title: Lonely Planet.
Includes index.
Keywords: South Africa -- Guidebooks; Lesotho -- Guidebooks; South Africa -- Description and travel; Lesotho -- Guidebooks